KEBIJAKAN HUKUM PIDANA DALAM UPAYA PENANGGULANGAN TINDAK PIDANA IMIGRAN ILLEGAL - MOHAMMAD AZIZUN HAKIM , Eko Soponyono, Purwoto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Formulation of the Law No. 6 of 2011 basically to accommodate any issues that arise in the field of immigration. Issues such as illegal immigrant crime, criminal forgery travel, and human trafficking. Explanation of illegal immigrants does not come clearly in the law, but can be encountered in the editorial section 113 is meant to crack down on those involved in the criminal illegal immigrants. This study uses normative juridical, by reviewing / analyzing secondary data, particularly primary legal materials in the form of legislation and secondary legal materials in the form of the Migration Act 1958 in Australia and the Law of Malaysia Act 574 Penal Code. From these results it can be concluded that the formulation of criminal illegal immigrants in Act No. 6 of 2011 on Immigration is not enough to accommodate all the problems in immigration crime, particularly in the case of illegal immigrants. Some disadvantages formulation criminal offenses related to illegal immigrants in the law relating to the qualification of crime is still unclear qualifications included in the violation or crime. Several weaknesses in this legislation can be improved in the future by considering the setting in some countries by comparing the law specifically governing criminal illegal immigrants. In line with the enactment of Law No. 6 of 2011 on Immigration is expected that this study also helped provide input in the formation undng laws that specifically criminalize illegal immigrants in the future.